(untitled) (Wire Insights: Journal of Innovation Insights, 2024)
Uzbekistan has its own system of public services went through a series of development processes with its independence. In these processes, the public service system showed its ways of integration, modernization and development. In the Republic of Uzbekistan, the system of public services was formed on the basis of its structure, organization, functionality and goals Ensuring the high quality of public services is often related to the demands and needs of our people and people. The "Society, Politics. Law" program developed by the President of the Republic of Uzbekistan, Shavkat Mirziyoyev, was implemented.